MODEL PENDIDIKAN KARAKTER KEWIRAUSAHAAN DI SEKOLAH MENENGAH KEJURUAN - Usman, Husaini; Raharjo, Nuryadin Eko (Jurnal Pendidikan Teknologi dan Kejuruan, 2012)
ABSTRACKOne of the strengths of Vocational High School compared to the general school is the students trainedto be entrepreneur. To support it, the learning model that needs to be developed is the character education forentrepreneurship. The purpose of this research is to gain the appropriate learning model to support charactereducation for entrepreneurship.This study was conducted by using grounded theory approach at Depok 2 VocationalHigh School, Sleman, Yogyakarta. The reserach subject was chosen by using snowball sampling technique throughthe setting of place, respondent and activitiy. Data analysis technique was using Miles Hubberman model.The result of the reserach showed that learning models to enhance character education for entrepreneurship atDepok 2 Vocational High School was using (a) role modelling,(b) Integrating learning inside and outside theclassroom, (c) school culture assimilization, (d) strengtening. This school needed to develop the learning modelfor entrepreneurship education which was synergic between character education and entrepreneurship learning.The integration was implmented by accomodating intervention: cultur:structure and figure. The implementationcovered: (1) classroom learning, (2) co curricul extracurricular, (3) learning through school culture, and (4)learning activities at home and in the community.Keywords: learning model, entrepreneurial character, vocational high schoolABSTRAK